2008
DOI: 10.1007/s00436-008-0942-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of sand flies in El-Nekheil province, in Al-Madinah Al-Munawwarah region, western of Saudi Arabia

Abstract: An entomological survey for sand flies was conducted at an area of cutaneous leishmaniasis--El-Nekheil in Northeast Al-Madinah Al-Munawwarah, Saudi Arabia. Standardized sampling with Centers for Disease Control (CDC) light traps and sticky traps was employed to determine monthly trends in species composition, density, sex ratio, and reproductive status and Leishmania infection rate of vector sand flies. A total of 621 sand flies were collected from March 2006 to November 2007. Six species representing two gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 25 publications
3
13
2
1
Order By: Relevance
“…The collected species reported here include the most important vectors of CL in the Middle East, which contribute to the persistence of the CL transmission cycle in Saudi Arabia. Here, P. papatasi was relatively less abundant than previously reported (El-Badry et al 2008), which is likely due to the difference in community structure and nature of habitats sampled, i.e., mostly wild. P. papatasi, the proven vector of L. major (Wahba et al 1990, was found to be widely distributed in peridomestic and domestic habitats (Janini et al 1995, Kamal et al 2003).…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…The collected species reported here include the most important vectors of CL in the Middle East, which contribute to the persistence of the CL transmission cycle in Saudi Arabia. Here, P. papatasi was relatively less abundant than previously reported (El-Badry et al 2008), which is likely due to the difference in community structure and nature of habitats sampled, i.e., mostly wild. P. papatasi, the proven vector of L. major (Wahba et al 1990, was found to be widely distributed in peridomestic and domestic habitats (Janini et al 1995, Kamal et al 2003).…”
Section: Discussioncontrasting
confidence: 79%
“…Our results suggest that the highest activity of the collected sand fly species occurs between May-August. Such a pattern of seasonal abundance was observed in different localities of Al-Baha by El-Badry et al (2008), in El-Nekheil and by other studies in Asir (Ibrahim & Abdoon 2005) and in Hail (Bakr 1995), Saudi Arabia. Identifying the seasonal abundance of the collected species is of importance for prediction of the period of maximum risk for leishmaniasis transmission and for the successful implementation of a control program.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Diversos estudios han incriminado a los flebótomos como hospederos y transmisores de innumerables otros 2,3,4,5 microorganismos . Cabe recordar que la picada de estos insectos pode causar irritación considerable y 6 reacciones alérgicas en personas sensibles .…”
Section: Introductionunclassified
“…Because Sergentomyia sand flies are widely distributed in the Old World and more abundant than Phlebotomus species in Africa and rainy temperate areas of South and Southeast Asia (Lewis 1974). Recent studies on distribution and population density of Sergentomyia species are reported in some regions, including Saudi Arabia (El-Badry et al 2008), Nepal (Pandey et al 2008) and Morocco (Boussaa et al 2009). Therefore, continuous studies are required to elucidate the role of Sergentomyia species in the transmission of Leishmania parasites.…”
Section: Discussionmentioning
confidence: 99%